TEMPERATURE CONTROL IN A 3-LAYER INSULATING NEONATAL ENCLOSURE TO IMPROVE THERMAL EFFICIENCY - MENDOZA, ZENON ANDRES CUCHO (2024)
THE WORLD HEALTH ORGANIZATION MENTIONS THAT THE MORTALITY OF PREMATURE NEWBORNS VARIES WIDELY BETWEEN 10% AND 90% DEPENDING ON THE COUNTRY AND ECONOMIC INCOME, OBSERVING THAT HIGH-INCOME COUNTRIES HAVE LOWER MORTALITY RATES IN NEWBORNS BORN PREMATURELY, DUE TO ACCESS TO ADVANCED MEDICAL RESOURCES AND BETTER NEONATAL MEDICAL CARE INFRASTRUCTURE. THEREFORE, IT IS IMPERATIVE TO RESEARCH AND USE CURRENT TECHNOLOGY FOR THE MANUFACTURE OF AFFORDABLE INCUBATORS IN OUR COUNTRY TO SAVE THE LIVES OF PREMATURE NEWBORN BABIES. A NEW NEONATAL INCUBATOR SYSTEM WITH THREE LAYERS OF INSULATION HAS BEEN DEVELOPED AND PATENTED IN THIS RESEARCH. BASED ON A 32-BIT MICROCONTROLLER AT91SAM3X8E OF THE ARDUINO DUE MODULE AS THE ELECTRONIC SYSTEM OF THE PROTOTYPE AND THE RTD-PT1000 DEVICE WAS USED TO READ THE SYSTEM. ACCORDING TO THE PROTOCOL OF THE IEC 60601-2-19 STANDARD, EXPERIMENTAL TESTS FOR NEONATAL INCUBATORS WERE CARRIED OUT. THE METHODOLOGY USED FOR THE ANALYSIS AND EVALUATION MADE IT POSSIBLE TO DEMONSTRATE THE THERMAL EFFICIENCY IN THE PROTOTYPE OF THREE INSULATING LAYERS BY OBTAINING RESULTS WITH AN ERROR LOWER THAN THOSE ESTABLISHED BY THE STANDARD. © 2024 IEEE.